Think tanks in Denmark – Media visibility and Network Relations - Blach-Ørsten, Mark; Nørgaard Kristensen, Nete (Politik, 2016)
Though think tanks have a long history internationally, they have especially in recent years come to play an increasingly important role in both policy-formulation and public debate. In this article, we analyse the growing presence of think tanks in a Danish context during the 2000s and the first half of the 2010s, because in this national setting think tanks are still a relatively new phenomenon. Based on theories of mediatization and de-corporatization, we present 1) an analysis of the visibility of selected Danish think tanks in the media and 2) an analysis of their political networks outside the media. The study shows that the two largest and oldest think tanks in Denmark, the liberal think tank CEPOS and the social democratic think tank ECLM, are very active and observable in the media; that the media’s distribution of attention to these think tanks, to some extent, confirms a re-politicization of Danish newspapers; but also that the news media as an arena of influence is only one part of the equation, since some of the corporatist political networks are still intact and working outside the media.